ELIMINATING GRAMMAR MISTAKES DURING THE SPEECH OFTHE 9TH CLASS PUPILS - Aydinova , Tursunoy (Educational Research in Universal Sciences, 2023)
This research paper explores an experimental approach to eliminate the grammar mistakes during the speech at teaching the 9th form pupils at specialized schools, namely avoiding grammar or spelling mistakes, such as tenses, verb «to be», misusing adjectives and adverbs and their degrees, using proper collocations or idioms and so on.